The effect of renewal privacy policy whatsapp to customer behavior - Hadion Wijoyo; Nandan Limakrisna; Suryanti Suryanti (Insight Management Journal, 2021)
Changes in WhatsAap policy cause confusion and tend to be anxious for users where each user is required to accept the WhatsAap management policy in order to link information on whatsAap with Facebook no later than February 8, 2021. With the number of users reaching millions of people this certainly affects decisions that are not easy. This study uses a qualitative method by conducting non-structured interviews with 10 informants who are the admin of the WhatsApp group which has a group of at least 100 people. Because the identity of the informant must be kept secret, the authors provide the code R1-R10. From the research results, it was found that consumers were aware of this Whatsapp policy and regretted this policy and would move to other safer and more comfortable applications